Análise da eficiência técnica de multinacionais do setor de healthcare com base em dados financeiros - Pinheiro, Roberta Rodrigues (Universidade Federal Rural do Semi-Árido, 2020)
This paper aims to analyze the efficiency of publicly traded multinationals in the health sector over the years. It highlights the importance of the health sector for a society and studies on efficiency, based on Banker, Charnes and Cooper who developed the method oriented to inputs, used in the study, as information was treated through a database taken from the platform Investing Brasil, which contains financial information on balance sheets already closed for companies on the stock exchange and the financial market. Obtaining positive results on their efficiency, 60% of the units studied are efficient since the initial year analyzed in the survey, without suffering any kind of fall during the period, it was also viable analyzed that only 20% of the units did not reach maximum efficiency until the end of the study, in addition to observing how time changes the variable, among those studied, that most impacts the efficiency indicator.
Keywords: Eficiência; Healthcare; Análise envoltória de dados; Efficiency; Healthcare; Data envelopment analysis; ENGENHARIAS::ENGENHARIA DE PRODUCAO